Dorsal Scapular Nerve Characterization as Indicator of Proximal C5 Injury and/or Early Recovery Post-Injury. (16th November 2020) - Jack, Andrew S; Jacques, Line G
Abstract: INTRODUCTION: C5 palsy (C5P) is a relatively common and debilitating postoperative spine complication. Although some prognostic factors have been identified helping to predict which patients may recover, controversy persists. As one of the most proximal nerve branches emanating from the C5 nerve root, the dorsal scapular nerve (DSN) would also be one of the earliest to demonstrate recovery. Although the DSN course has been characterized more distally, a paucity of literature regarding its origin and proximal branching pattern exists. METHODS: Eighteen cadaveric dissections were performed. A posterior cervical approach was used for brachial plexus and DSN exposure. Digital calipers were used for DSN branching and course characterization with descriptive statistical analysis completed for the following measurements: size of the DSN (diameter), size of C5 root (diameter), distance of DSN branch-point from C5 ganglion (pre- vs postganglionic), distance of DSN branch-point from dural edge and C5 root-SC branch-point, and distance of DSN branch-point to the posterior foraminal tubercle (intra- vs extraforaminal). MRI tractography was also performed for radiological-anatomical DSN measurement correlation. RESULTS: The median diameter of the DSN was 3.7mm, whereas the C5 was 6.8mm. The majority (17/18, 94%) of the DSNs observed branched from the C5 root a median 12.6mm distal to the dorsal root ganglion (postganglionic); the majority (12/18, 67%) of DSNs observed branched from the C5 root within the foramen a median 4.3mm proximal to the foraminal (intraforaminal). Moreover, the median distance from DSN branch-point to the dural edge was 17.3mm, and 20.5mm to the C5 root take-off from the SC. CONCLUSION: Upon anatomical dissection, the DSN was determined to be the most proximal C5 nerve branch with the majority emanating intraforaminally and in close proximity to the dorsal root ganglion. The DSN and its targets could serve as indicator of proximal nerve root injury and/or early recovery after injury.